2006
DOI: 10.1530/rep.1.01118
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficiency of bovine cloning by autologous somatic cell nuclear transfer

Abstract: Somatic cell nuclear transfer (SCNT) has been used for the cloning of various mammals. However, the rates of successful, healthy birth are generally poor. To improve cloning efficiency, we report the utilization of an 'autologous SCNT' cloning technique in which the somatic nucleus of a female bovine donor is transferred to its own enucleated oocyte recovered by ovum pick up, in contrast to the routine 'allogeneic SCNT' procedure using oocytes from unrelated females. Our results showed that embryos derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
1
19
0
4
Order By: Relevance
“…An explanation for the highest developmental competence of hybrid oocytes is due to the genetic heterogeneity of the hybrid recipient cytoplasm which provides more opportunities for reprogramming and embryo development. Another possible explanation, based on our further studies, is the nuclear-mitochondrial interactions are normal because in hybrid cloned embryos, both nuclear and mitochondrial components came from same breed (due to the exclusively maternal inheritance of mitochondria) (Yang et al, 2006;Yan et al, 2010).…”
Section: Mitochondriamentioning
confidence: 84%
“…An explanation for the highest developmental competence of hybrid oocytes is due to the genetic heterogeneity of the hybrid recipient cytoplasm which provides more opportunities for reprogramming and embryo development. Another possible explanation, based on our further studies, is the nuclear-mitochondrial interactions are normal because in hybrid cloned embryos, both nuclear and mitochondrial components came from same breed (due to the exclusively maternal inheritance of mitochondria) (Yang et al, 2006;Yan et al, 2010).…”
Section: Mitochondriamentioning
confidence: 84%
“…It is important to ensure that the somatic nucleus is capable of sufficiently regulating the oocyte mtDNA. The importance of mtDNA composition has been indirectly shown in cloning experiments where autologous SCNT (somatic cells and oocyte derived from the same female donor) developed at higher frequencies, both at blastocyst stage and to term [85], compared to heterologous SCNT (donor cell not related to recipient cytoplasm).…”
Section: Mitochondrial Dna (Mtdna) Composition Of the Reconstructed Ementioning
confidence: 99%
“…Efficiency of bovine cloning has also been also improved by autologous SCNT. The individual oocyte donor and oocyte mitochondrial DNA haplotypes significantly affect the efficiency of SCNT [3,4].Recent studies have demonstrated that highly efficient cloning can be achieved by optimization of the actual cloning procedure. Recently, a new cloning technology referred to as "handmade cloning" (HMC) has been preferred because of its low cost and ease of operation.…”
mentioning
confidence: 99%
“…Efficiency of bovine cloning has also been also improved by autologous SCNT. The individual oocyte donor and oocyte mitochondrial DNA haplotypes significantly affect the efficiency of SCNT [3,4].…”
mentioning
confidence: 99%